Pengaruh Personal Branding di Instagram terhadap Minat Konsumen Menggunakan Jasa Makeup MUA di Kota Padang - Lismaryati Lismaryati; Rahmi Oktarina (Lembaga Yasin AlSys, 2026)
The increasing competition in beauty services in Padang City requires makeup artists (MUAs) to develop effective promotional strategies, one of which is personal branding on Instagram to attract consumer interest. This study aimed to analyze the effect of Instagram personal branding on consumers’ interest in using MUA makeup services in Padang City. The study employed a quantitative method with a causal associative approach. The sample consisted of 81 respondents selected through purposive sampling. Data were collected using a questionnaire and analyzed with SPSS version 25 through validity, reliability, classical assumption, and hypothesis testing (t-test). The results showed that the Instagram personal branding and consumer interest variables were in the very good category, with all items declared valid and reliable (α = 0.903 and α = 0.952) and meeting the classical assumption test requirements (sig. > 0.05). The hypothesis test showed a significance value of 0.00 (< 0.05) and a coefficient of determination (R²) of 0.847, indicating that 84.7% of the variation in consumer interest was explained by Instagram personal branding. These findings confirm that Instagram personal branding has a positive and significant effect on consumer interest; therefore, the stronger and more consistent the personal branding developed, the higher consumers’ interest in using MUA services in Padang City.